Marcadores moleculares, imunológicos e genéticos das reações hansênicas - SOUSA, Ana Lúcia Osório Maroclo de (2009)
Type 1 (T1R) and Type 2 (T2R) leprosy reactions are complications in the clinical management of leprosy patients because they can lead to neural damage and impairment, resulting in irreversible deformities and disabilities. This thesis, presented as research article/manuscript has investigated potential markers for the diagnosis and prognosis of leprosy reactions. In the first study, we evaluated a multicentric cohort of leprosy patients with single skin lesion which is considered the earliest clinical manifestation of the disease. In this study, at the moment of diagnosis a skin biopsy was collected for histopathology and for the investigation of Mycobacterium leprae DNA by polymerase chain reaction (ML-PCR). After diagnosis patients were treated with single dose of Rifampicin, Ofloxacin and Minocyclin (ROM) and were clinically monitored during 3 years .During follow up, around 15% of patients developed T1R. In multivariate analysis, age > 40 years and MLPCR positivity were associated with T1 manifestation. The second study aimed to identify potential circulating markers associated with leprosy reactions. Plasma levels of 27 cytokines/chemokines/growth factors were quantified by multiplex assay. A nested case control study compared the levels of these factors in leprosy patients with or without T1R and T2R. Leprosy patients were paired by sex, age group (+/- 5 years) and histopathological classification. Significant differences in plasma levels of CXCL10 (p=0.004) and IL6 (p=0.013) were observed in patients with T1R compared with controls without reaction. IL7 levels (p=0.039) and PDGF-BB (p=0.041) were increased in T2R and marginally significant for IL6 (p=0.05). This investigation indicated that CXCL10, IL6 and IL7 may represent potential plasma biomarkers of leprosy reactions. The third study investigated the influence of single nucleotide polymorphism (SNP) in the IL6 gene and the development of leprosy reactions. For this purpose a nested case control study was performed based on a cohort of 409 leprosy patients recruited in Goiânia-GO. After leprosy diagnosis patients were monitored during multidrug therapy regarding the appearance of leprosy T1R and T2R. Evidences of positive associations were observed for leprosy T2R and tag SNPs markers- rs 2069832 (p=0.002), rs 2069840 (p=0.027) and rs 2069845 (p=0.044). These IL6 gene tag SNPs capture information of the whole gene locus. Positive association with T2R was also seen for the functional variant of IL6 gene- tag SNP rs 1800795 (p=0.005). Additionally, IL6 plasma levels among TR2 patients and controls without reaction correlated with different IL6 genotypes. No association was observed between IL6 gene variants and leprosy T1R. The description of genetic predictive factors of leprosy reactions may contribute to the development of preventive strategies against these leprosy incapacitating events.